Family Center Maternity Care (FCMC) is Effective in Reducing Anxiety in Pregnant Women - Kamsatun, Kamsatun; Susanti, Susi; Fattah, Vera Fauziah; Februati, Sofia (Poltekkes Kemenkes Jakarta III, 2023)
The COVID-19 pandemic poses a risk to pregnant women due to physiological and immunological changes that can increase the risk of obstetric complications from respiratory infections in pregnant women. Anxiety for pregnant women during the Covid pandemic can impact pregnancy disorders until postpartum, such as anxiety can be anticipated during pregnancy. Care support from family, friends, and health workers, both physically and psychosocially, is needed for pregnant women. The research method is quasi-experimental with a pre-post test two-group design. The population is pregnant women in Gajah Village, Kutawaringin sub-district, Bandung Regency, with a sample of 30 people per group, using a purposive sampling technique. Before the intervention, pregnant women were given a pre-test using a questionnaire. The time to fill out the questionnaire is approximately 15 minutes. The FCMC intervention is in the form of providing education using the module and assisting pregnant women. The duration of education and assistance for pregnant women is approximately 30 minutes. Education and assistance are carried out twice an interval of 1 week. Post-test was conducted to determine the anxiety of pregnant women—analysis with T-test dependent test and independent T-test. The results showed an effect of the FCMC intervention on reducing the anxiety of pregnant women, with a p-value of 0.000. FCMC interventions and modules can be a reference in improving services for pregnant women and support for pregnant women and their families in preventing anxiety.